Perilaku Kekerasan Verbal Orang Tua Terhadap Kepercayaan Diri Anak Usia 5-6 Tahun - Fajarrini, Arsyia; Ichsan, Ichsan (Zuriah : Jurnal Pendidikan Anak Usia Dini, 2023)
There are still many parents in Indonesia who discipline their children in the wrong way, one of which is verbal violence. The purpose of this study was to find out the forms of verbal violence, parents' educational and economic background. As well as to find out how the ability of children to interact with their social environment. The research method used in this study is a qualitative case study. The research subjects were families who had daughters aged 5 years and 8 months in Joyoakan, Serengan, Surakarta District. Data collection techniques using direct and non-participant observations and interviews. Data analysis techniques by collecting data, perfecting data, processing data, compiling data analyzing the data obtained and concluding research results. Meanwhile, to check the validity of the data, researchers used the source triangulation technique. The results of this study describe when and the forms of verbal violence that parents did against "J". The background of the parents is ultimately seen in the parenting style and causes of verbal abuse in children. Seeing how communication and closeness is built between parents and "J" and we can see how the child's response after getting verbal violence when in a social environment.